Impact of treadmill running on distal femoral cartilage thickness: a cross-sectional study of professional athletes and healthy controls - Pouria Azami; Alireza Ashraf; Omid Yousefi; Alireza Hosseinpour; Aref Nasiri (BMC, 2024)
Abstract Purpose This present study aimed to assess the impact of treadmill running on distal femoral cartilage thickness. Methods Professional athletes aged 20 to 40 years with a history of treadmill running (minimum 75 min per week for the past three months or more) and age-, sex-, and body mass index (BMI)-matched healthy controls were recruited. Demographics and clinical features of participants were recorded. Athletes were divided into subgroup 1 with less than 12 months of treadmill running and subgroup 2 with 12 months or more of treadmill running. Distal femoral cartilage thicknesses were measured at the midpoints of the right medial condyle (RMC), right intercondylar area (RIA), right lateral condyle (RLC), left medial condyle (LMC), left intercondylar area (LIA), and left lateral condyle (LLC) via ultrasonography. Result A total of 72 athletes (mean age: 29.6 ± 6.6 years) and 72 controls (mean age: 31.9 ± 6.7 years) were enrolled. Athletes had significantly thinner cartilages in the RLC (2.21 ± 0.38 vs. 2.39 ± 0.31 cm, p = 0.002), LLC (2.28 ± 0.37 vs. 2.46 ± 0.35 cm, p = 0.004), and LMC (2.28 ± 0.42 vs. 2.42 ± 0.36 cm, p = 0.039) compared with the control group. Furthermore, cartilage thickness was significantly thinner in subgroup 2 athletes compared with the control group in the RLC (2.13 ± 0.34 vs. 2.39 ± 0.31 cm, p = 0.001), LLC (2.22 ± 0.31 vs. 2.46 ± 0.35 cm, p = 0.005), and LMC (2.21 ± 0.46 vs. 2.42 ± 0.36 cm, p = 0.027); however, subgroup 1 athletes did not have such differences. There was a weak negative correlation between total months of treadmill running and cartilage thickness in the RLC (r = − 0.0236, p = 0.046) and LLC (r = − 0.0233, p = 0.049). No significant correlation was found between the distal femoral cartilage thickness at different sites and the patients' demographic features, including age, BMI, speed and incline of treadmill running, and minutes of running per session and week (p > 0.05). Conclusion Compared with healthy controls, professional athletes with a history of long-term high-intensity treadmill running had thinner femoral cartilages. The duration (months) of treadmill running was weakly negatively correlated with distal femoral cartilage thickness. Longitudinal studies with prolonged follow-ups are needed to clarify how treadmill running affects femoral cartilage thickness in athletes.